Recovery of nutrients from wastewater - Lim, Melissa Hui Ting. (2010)
Recovery of nutrients from wastewater is an efficient process to reduce the presence of nutrients, particularly ammonium and phosphate in the environment. By reducing nutrients disposed into the environment, the naturally occurring phenomenon of eutrophication could be slowed, and potential economic benefits could be gained. Several methods are available for nutrient removal from wastewater, but only some methods allow for nutrient recovery. In this report, the feasibility of using struvite and ammoniojarosite to recover nutrients such as ammonia and phosphate from Singapore’s wastewater were explored. At optimal conditions, experiments on struvite yielded promising results, with 90% phosphate recovery and 10% ammonium recovery. As for ammoniojarosite, it was noted that no previous experiment was documented on using wastewater as a source of ammonium for its formation. However, experiments done on wastewater using conditions recommended for manufacturing synthetic ammoniojarosite achieved 16% ammonium recovery. Through recovery of nutrients from Singapore’s wastewater, nutrient loading to treatment plants could be reduced. Products of the processes could also be sold as fertilisers.